Uso da monitorização residencial da pressão arterial (MRPA) na avaliação do controle de hipertensos - CARNEIRO, Laís Nogueira Chaves (2024)
Introduction: Systemic Arterial Hypertension (SAH) is a highly prevalent chronic disease and is considered the leading cause of cardiovascular and cerebrovascular diseases, which are the main causes of death in Brazil. Thus, controlling blood pressure levels is crucial to prevent or delay the onset of chronic complications. Despite this, there is a low rate of disease control, and Home Blood Pressure Monitoring (HBPM) is recognized not only as a tool for assessing blood pressure levels but also for improving hypertensive patients' adherence to treatment. Objective: To identify uncontrolled hypertensive patients and the factors related to low treatment adherence, based on the use of HBPM. Methods: This is a prospective, observational, cross sectional, descriptive study with a quantitative approach, through blood pressure measurement and the application of a structured interview with hypertensive patients treated by the Family Health Strategy at the Camaçari Basic Health Unit, in Imperatriz, MA. Results: A total of 133 individuals were included in the study. In this sample, patients had an average age of 62 years. The majority were elderly, female, of mixed race, with elementary education, retired or pensioners. In about 80% of the cases, both the family and patient income were at most two minimum wages. Most had been in treatment for more than 5 years (56.4%), were on monotherapy, were non-smokers, did not consume alcohol, and were sedentary. Cardiovascular risk was classified as high in 60.2% of the patients. Most of them had moderate or high adherence to treatment and had controlled blood pressure (64.7%). Among hypertensive patients with blood pressure within the control target, the majority were female and had low or medium cardiovascular risk. Moreover, a greater proportion of patients with moderate or high treatment adherence, according to the Morisky Scale, had controlled blood pressure. Additionally, male gender and alcohol consumption were associated with low treatment adherence. Final considerations: The study on the use of HBPM (Home Blood Pressure Monitoring) concludes that this tool is effective in identifying controlled and uncontrolled hypertensive patients. Although many patients have achieved blood pressure control, the rates are still insufficient, highlighting the need for health education and training.